Increasing value, reducing waste: tailoring the application of dental sealants according to individual caries risk. (9th September 2020) - Yansane, Alfa; Listl, Stefan; Dawda, Dyutee; Brandon, Ryan; White, Joel; Spallek, Heiko; Walji, Muhammad F.; Kalenderian, Elsbeth
Abstract: Objectives: Despite a significant national investment in oral health, there is little understanding of the return in terms of quality. Value‐based payments aim to refocus provider reimbursement based on the value created to the patient. Our objectives were to apply a set of dental quality measures to help determine the value of preventive dental care provided to children at two academic dental school clinics. Methods: We queried the institutional electronic health records (EHRs) for patients between the ages of 6–14 years with sealable first or second permanent molars, determined caries risk status, identified if dental sealants were placed, and finally if the teeth showed evidence of new caries experience. In order to determine the cost‐effectiveness of EHR‐based triage of applying dental sealants, we calculated the incremental cost‐effectiveness ratio (ICER) for the dental quality measures supported sealing program. Results: Between the two academic sites, there were 6, 155 unique children for a total of 12, 302 eligible teeth without a sealant and 32, 811 eligible teeth with a sealant. Teeth without a sealant were more likely to have decay (4.8 percent) than those with a sealant (1.7 percent). At both sites, patients with high caries risk were more likely to benefit from sealants compared to those patients with low risk. Conclusion: Implementation of caries risk stratified fissure sealant quality measures demonstrates the potential for extracting better value in oral health care.